PEMANFAATAN TERAPI SHIATSU SEBAGAI TINDAKAN PREVENTIF CEDERA OTOT - Nasywa Yudeldi; Ade Teti Vani; Dessy Abdullah; Rosmaini, Rosmaini; Nadia Purnama Dewi; Yuliza Birman; Melya Susanti; Rinita Amelia (Yayasan Nusantara Hasana Berdikari, 2025)
Shiatsu therapy is a complementary treatment approach rooted in Japanese tradition, based on the principle of applying pressure to specific points on the body to stimulate energy flow, improve health, and support well-being. This study aims to explore the effect of shiatsu therapy on reducing the risk of injury. This study utilized a qualitative methodology, conducting a literature review of journals published between 2015 and 2025 related to shiatsu therapy. The search employed the keywords